The 30-day ketogenic cleanse : reset your metabolism with 160 tasty whole food recipes & a guided meal plan - Emmerich, Maria (Victory Belt Publishing Inc., 2016)
The 30-Day Ketogenic Cleanse is a guidebook for healing your body from the inside out with a high-fat, moderate-protein, low-carbohydrate diet. Sadly, most people who attempt a keto diet do it incorrectly. Keto expert Maria Emmerich, on the other hand, has based this cleanse on a true, well-formulated ketogenic diet, which will help you reset your metabolism, regain good health, boost your energy, and shed unwanted weight, all without feeling restricted or deprived"--Page 4 of cover.